Phytochemical analysis, antioxidant and antimicrobial activities of Ammannia baccifera L. - Chaudhary, Umesh; Rajbhandari, Meena (Scientific World, 2025)
Ammannia baccifera has wide application in ethnomedicine around the globe and it has been investigated for various pharmacological activities. However, A. baccifera from Nepal is not investigated phytochemically and biologically. Here we report about the screening of extracts for phytochemicals, estimation of phenolics, flavonoids, tannins and sugars as well as antioxidant and antibacterial activities of different extracts. In phytochemical screening, phenolics, flavonoids, glycosides, saponins, quinones, reducing sugar, tannins, steroids and coumarin were detected in methanol and 50% aqueous methanol extracts so these extracts were further investigated for phenolics, flavonoids, tannins and sugars contents. Methanol extract showed the presence of higher amounts of phenolics (178.65 ± 1.16 mg GAE/g), flavonoids (60.05 ± 2.24 mg CE/g) and tannins (194.29 ± 2.96 mg TAE/g) than the 50% aqueous methanol extract (107.66 ± 2.04 mg GAE/g, 23.95 ± 2.07 mg CE/g, 120.28 ± 2.25 mg TAE/g). Similarly, 50% aqueous methanol extract showed the presence of higher amounts of sugars than (206.86 ± 4.21 mg GE/g) methanol extract (153.03 ± 3.80 mg GE/g). In DPPH free radical scavenging assay, methanol extract showed lower IC50 values (95.52±6.27μg/mL) than 50% aqueous methanol extract (114.66±8.49 μg/mL). In antibacterial assay, methanol extract showed activity against Gram positive bacteria, B. subtilis, S. aureus and S. epidermidis with inhibition zone ranged from 12-20 mm but the extract was inactive against Gram negative bacteria and fungi. The minimal inhibitory concentration of the extract against all three Gram positive bacteria was found to be between 1.56 to 0.78 mg/mL. The findings of this study support the traditional use of this plant to treat skin diseases.